Mechanical properties of thin wall ductile iron-influence of carbon equivalent and graphite distribution - David, P. (2004)
This work focuses on the study of the mechanical properties and microstructure of plates of thin wall ductile iron, cast in sand moulds of vertical and horizontal configuration. All tests were carried out on ferritised samples. Melts of carbon equivalent values ranging from 4.06 to 4.85 were used to cast plates of thickness ranging from 1.5 to 4 mm. The results show that irons having carbon equivalent values greater than 4.6 exhibit a marked tendency to develop exploded graphite shapes and agglomeration of graphite nodules. As a result, these irons show scattered values of mechanical properties. As irons are produced with carbon equivalent values below 4.6%, the mechanical properties improve, reaching levels that satisfy the requirements of standards developed for ferritised ductile irons sand cast in Y-blocks.